Reduction of neck pain severity in patients with medication-overuse headache - Yooha Hong; Hong-Kyun Park; Mi-Kyoung Kang; Sun-Young Oh; Jin-Ju Kang; Heui-Soo Moon; Tae-Jin Song; Mi Ji Lee; Min Kyung Chu; Soo-Jin Cho (The Journal of Headache and Pain)
Abstract Background Neck pain and primary headache disorders are highly prevalent in populations and clinical cohorts. Medication-overuse headache (MOH) is a treatable secondary headache, mainly developing in migraine sufferers, that accounts for the majority of patients presenting to headache clinics. Nevertheless, the association between neck pain and MOH has not been reported. This study evaluated the prevalence and clinical course of neck pain in patients with MOH before and after MOH treatment. Methods We analyzed 635 MOH patients enrolled in a nationwide, prospective, multicenter MOH registry. Demographics and clinical data were collected at baseline and 3 months to evaluate changes in the status and severity of neck pain and headache. Severity of neck pain was graded into 4 groups, and severe neck pain was defined as grade 3 or 4. Results Among 635 patients with MOH, 366 (57.6%) reported neck pain at baseline. MOH patients with neck pain had an earlier onset of their primary headache disorder (23.4 ± 12.7 vs. 26.2 ± 13.3 years, p = 0.007). Although monthly headache days were comparable between the patients with neck pain and those without neck pain, the neck pain group had higher levels of anxiety (7.4 ± 5.8 vs. 6.4 ± 5.4, p = 0.017), more severe cutaneous allodynia (2.4 ± 3.3 vs. 1.8 ± 3.0, p = 0.038), and poorer quality of life (171.7 ± 70.4 vs. 184.0 ± 68.9, p = 0.029). At 3 months, 456 (71.8%) were followed-up, and 257 (56.4%) were recovered from MOH. Compared to the baseline, the proportion of severe neck pain (40.4% vs. 19.4%, p < 0.001) was decreased. The proportion of severe neck pain was much lower in patients with recovery from MOH compared to those without (4.7% vs. 15.1%, p < 0.001). Conclusions Neck pain in MOH patients was associated with earlier onset of headache, higher levels of anxiety and allodynia, and poorer quality of life. Improvement in neck pain improvement was linked to recovery from MOH. These findings suggest the potential importance of integrating and management of neck pain into clinical practice for MOH.